The clinical effects of Orff music therapy on children with autism spectrum disorder: a comprehensive evaluation - Fan, Qiongli; Ding, Mengying; Cheng, Wang; Su, LiSha; Zhang, Yuping; Liu, Quanxing; Wu, Zhifeng (Frontiers in Neurology, 2024)
Objective This study aimed to investigate the clinical effects of Orff music therapy on children with Autism Spectrum Disorder (ASD) from the perspectives of parents, evaluators, and therapists. Methods 93 children with ASD aged 3–6 years participated in the study. They were divided into an observation group (n = 48) receiving comprehensive rehabilitation intervention including Orff music therapy, and a control group (n = 45) receiving only comprehensive rehabilitation intervention. The Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Psycho-educational Profile-3rd edition (PEP-3) were used for assessments before and after the intervention. Results There were no significant demographic differences between the two groups. Both groups showed significant improvements in Sensory, Relating, Language, CVP, EL, RL, VMI, AE, SR, and CARS scores at T1, T2, and T3 (T1 vs. T2, T2 vs. T3, T1 vs. T3) (all p < 0.05). The observation group demonstrated significant changes in Body and Object use and FM, while the control group showed some changes in these domains. Social and self-help, GM, CMB, and CVB also significantly improved in both groups after 6 months of intervention (all p < 0.05). In terms of different time intervals, the observation group showed greater improvements in Sensory, Relating, Language, CARS scores, EL, RL, and SR compared to the control group (all p < 0.05). The improvement levels in Body and Object use, CVP, FM, VMI, and AE did not differ significantly between the two groups in the T1–T2 interval, but were significantly higher in the observation group in the T2–T3 and T1–T3 intervals (all p < 0.05). The magnitude of changes in Social and self-help, GM, CMB, and CVB did not differ significantly between the groups. Conclusion Orff music therapy showed significant improvements in language expression, language comprehension, social skills, cognitive abilities, imitation abilities, emotional expression and fine motor in children with ASD. These findings provide support for the use of Orff music therapy as an effective intervention for children with ASD.